Remote sensing for prediction of floods in the Jhelum River and the significance of the Pir Panjal depression - Siddiqui, Nusrat K. (Journal of Nepal Geological Society, 2000)
The Mangla Dam is constructed across the Jhelum River in Pakistan and has a catchment area of about 33,334 sq. km. It is also fed by the Neelum, Kunhar, and Punch Rivers. Flooding downstream of the dam is a recurring phenomenon. The Jhelum River originates in the Pir Panjal depression and covers an area of 12,650 sq. km. The depression constitutes about 38% of the Mangla Dam's overall catchment area and 65.5% of the Jhelum River's sub-catchment area. The satellite imageries, meteorological data, vegetation cover, and thermal infrared images indicate that the depression has its own typical characteristics and an equally anomalous response, particularly in terms of water discharge. The floodwater from the Pir Panjal depression constitutes less than 50% of the Mangla Reservoir's summer discharge. Vigilant remotely sensed information and images from weather satellites, water flow measurements at strategically located ground stations, and close coordination amongst the Irrigation Department, water management authorities, the Meteorological Department, and in particular with the agencies acquiring remotely sensed data may provide a practical remedy for the recurring calamity downstream of the Mangla Dam.